How can gamified applications drive engagement and brand attitude? The case of Nike Run Club application - Ivo Rodrigues; Jo\~ao M. Lopes; Ana Borges; José Castro Oliveira; Márcio José Sol Pereira Oliveira (Administrative Sciences, 2021)
This research aims to analyze the feasibility of gamified applications as a tool to promote engagement and brand attitude. To accomplish this, this research was developed using a quantitative methodology. A confirmatory factor analysis (CFA) was performed and the model hypotheses were tested by a structural equation modeling (SEM). A questionnaire was applied to Portuguese consumers who use the "Nike Run Club" application, from which 203 valid responses were received. The results confirm the influence of social circles and their impact on the intention to interact with the brand. For theoretical contributions, this research contributes to the existing literature and academic knowledge in the areas of marketing and gamification, providing a suggestion for the TAM model to be used in this type of research. It also contributes to a better understanding of the relationship between gamification and marketing, demonstrating that the use of gamified applications as engagement tools can have a positive impact on the brand attitude. On the practical side, it contributes as a consultation tool for brands, application designers, and marketers when defining engagement strategies, allowing a better understanding of the factors that may or may not influence the public's relationship with the brands and what dynamics they should use in the development of new Gamified marketing solutions.
Keywords: 350; brand attitude; companies; COVID-19; engagement; gamification; marketing; mobile apps